A Bird's-Eye View of Personal Pronouns and Accusative Markers in Ancient Semitic Languages. (15th February 2018) - Cohen, Ohad
Abstract: In this comparative study of ancient Semitic languages, I present data on the development of personal pronouns and accusative markers. My meta-analysis combines what is known about the major representative languages from both East and West Semitic languages in order to focus on three gradual, corresponding developments: (1) the erosion of inflected oblique independent personal pronouns; (2) the disappearance of the case-ending system; and (3) the emergence of the independent object marker. A bird's-eye view of the documented evidence on Semitic languages suggests that in West Semitic languages, both the oblique independent personal pronoun and the case-ending system gradually disappeared. In parallel, a set of object markers was introduced into West Semitic. This process will be shown to progress at a different pace for the various languages in this branch, and to be relevant not only to the North-west Semitic branch, but rather to the span of old West Semitic languages.